1965
DOI: 10.2466/pms.1965.20.3.697
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Auditory and Visual Autokinetic Effects

Abstract: This study involved an investigation of the relationships between visual and auditory autokinetic phenomena. An apparatus was designed to obtain quantifiable records of the perceived auditory autokinetic loudness and pitch effects. Several methods were devised to score these records. When the auditory and visual autokinetic scores were correlated, all of the obtained coefficients were positive, four correlations were significant at the .05 level (only one was expected by chance), and one correlation at the .01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1966
1966
1973
1973

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…McKi trick (196S) found little relationship between autokinesis and body activity, reversible figures, and visual figural aftereffects. Anderson (1965), however, found a tendency for cross-modal positive correlation between various measures of auditory and visual autokinesis. Farrow, Santos, Haines, and Solley (1965) found that latency of autokinesis decreased with practice under both massed and spaced conditions of practice.…”
Section: Subject Factorsmentioning
confidence: 82%
“…McKi trick (196S) found little relationship between autokinesis and body activity, reversible figures, and visual figural aftereffects. Anderson (1965), however, found a tendency for cross-modal positive correlation between various measures of auditory and visual autokinesis. Farrow, Santos, Haines, and Solley (1965) found that latency of autokinesis decreased with practice under both massed and spaced conditions of practice.…”
Section: Subject Factorsmentioning
confidence: 82%
“…Autokinesis is one of many of these effects. Although visual autokinesis has been studied most extensively, autokinetic movement has been reported for auditory and tactual stimuli (Anderson, 1965;Spigel, 1965). Reports of rotation in the absence of angular acceleration are well known to investigators of the perception of rotation, but no systematic investigations of such autokinetic movements have been found.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study by Anderson & Moss (1964), auditory movement was observed by 28 of the 36 Ss. Anderson (1965) also investigated correlational relationships b etween visual and auditory autokinesis. Using reported changes in pitch and loudness as auditory criteria, he found positive correlations, but not all of them were significantly different from zero.…”
mentioning
confidence: 99%